Art and architectural traditions of India and Iran
1 online resource
Keywords: This book presents a comprehensive overview of the historical and cultural linkages between India and Iran in terms of art and architectural traditions and their commonality and diversity. It addresses themes such as early connections between Iran, India and Central Asia; study of the Qutb Complex in Delhi; the great immigration of Turks from Asia to Anatolia; the collaboration of Indian and Persian painters; design, ornamentation techniques and regional dynamics; women and public spaces in Shahjahanabad and Isfahan; the noble-architects of emperor Shah Jahan's reign; development of Kashmir's Islamic religious architecture in the medieval period; role of Nur Jahan and her Persian roots in the evolution of the Mughal Garden; synthesis of Indo-Iranian architecture; and confluence of Indo-Persian food culture to showcase the richness of art, architecture, and sociocultural and political exchanges between the two countries. Bringing together a wide array of perspectives, it delves into the roots of connection between India and Iran over centuries to understand its influence and impact on the artistic and cultural genealogy and the shared past of two of the oldest civilizations and regional powers of the world. With its archival sources, this book will be useful to scholars and researchers of medieval history, Indian history, international relations, Central Asian history, Islamic studies, Iranian history, art and architecture, heritage studies, cultural studies, regional studies, and South Asian studies as well as those interested in the study of sociocultural and religious exchanges.